Polycyclic aromatic hydrocarbons and heavy metals in the Cispata Bay, Colombia: A marine tropical ecosystem. Issue 1 (15th July 2017) - Burgos-Núñez, Saudith; Navarro-Frómeta, Amado; Marrugo-Negrete, José; Enamorado-Montes, Germán; Urango-Cárdenas, Iván
Abstract: The concentrations of polycyclic aromatic hydrocarbons and heavy metals were evaluated in shallow sediments, water, fish and seabird samples from the Cispata Bay, Colombia. The heavy metals concentrations in the sediment was in the following order: Cu > Pb > Hg > Cd. The heavy metal concentration was different (p < 0.05) in juvenile and adult birds. High concentrations of mercury were registered in the seabird (10.19 ± 4.99 mg kg − 1 ) and fish (0.67 μg g − 1 ) samples. The total concentration of polycyclic aromatic hydrocarbons ranged from 7.0–41 ng g − 1 in sediment, 0.03–0.34 ng mL − 1 in water samples, 53.24 ng g − 1 in fish, and 66 ng g − 1 in seabirds. The high concentrations of heavy metals in seabirds may be explained by their feeding habits. The presence of polycyclic aromatic hydrocarbons in the Cispata Bay may be due to hydrocarbon spills during oil transport at the nearby oil port. Highlights: HM and PAH present in different seabird and seafish species in the Cispata Bay, Colombia. Sediment and water of Cispata Bay are impacted by PAH due to natural and petrogenic origin Differences in HM levels of feathers of juvenile and adult birds suggesting that metal accumulation depends on exposure time